Morphological Distribution and Formation Mechanisms of Antimony in the Shallow Groundwater of the Xikuangshan Antimony Mine in Hunan, China - Sun, Ximeng; Li, Yi; Liu, Chao; Zhang, Lu; Li, Ziyao; Hao, Chunming (Frontiers in Environmental Science, 2022)
The century-old mining development and utilization of antimony (Sb) ore in Xikuangshan (XKS) mine, groundwater antimony pollution has attracted great attention. At present, the sources and geochemical behaviors of high Sb groundwater in this area have been widely recognized, but morphological distribution and formation mechanisms of Sb(V) and Sb(III) in shallow groundwater were still little known. Forty-three groundwater samples of Magunao aquifer (D3x4) were collected between June and September 2020 to determine morphological distribution and formation mechanisms of Sb valence state in the recharge area, runoff area and discharge area. The range of Sb content in the recharge area, runoff area, and discharge area of the D3x4 water was 3.300×10-3–7.982 mg/L, 1.760×10-2–17.326 mg/L and 1.230×10-2–16.773 mg/L, respectively. The D3x4 water is dominated by Sb(V), which form was Sb(OH)6-. The Sb(V) mainly comes from the oxidative dissolution of Sb2S3, the mining activities, and the leaching of arsenic alkali residues. The silicate mineral weathering, carbonate mineral dissolution, and ion exchange promote the dissolution of Sb2S3. At the same time, redox and competitive adsorption in the runoff area increase the Sb(V) content in the water environment. The results of this research provide an understanding of the mechanism of Sb pollution in shallow groundwater and will help in controlling water-environment pollution and securing water-resource in mining areas.